THERAPEUTIC POTENTIALS OF Garcinia cambogia (L.) Roxb.: PHYTO- CHEMICAL CHARACTERIZATION AND BIOLOGICAL ACTIVITIES (Applied Biological Research, 2025)
Garcinia cambogia, traditionally utilized for its medicinal properties, has garnered scientific interest for its potential health benefits. This study aimed to bridge the gap between traditional use and scientific validation by characterizing the phytochemical composition of G. cambogia hydro-alcoholic fruit extract and evaluating its antioxidant, anti-inflammatory, and antidiabetic properties.Phytochemical analyses identified numerous bioactive compounds within the fruit extract. The extract exhibited high total phenolic and flavonoid content, indicative of its potent antioxidant capacity. In antioxidant assays, the extract demonstrated significant activity, outperforming standard references. Enzyme inhibition assays revealed notable α-amylase and α-glucosidase inhibitory activities, suggesting its antidiabetic potential. Furthermore, in an in vivo model, the extract significantly reduced inflammation, comparable to standard anti-inflammatory drugs.These findings support the therapeutic potential of G. cambogia in managing oxidative stress, inflammation, and diabetes, providing a scientific basis for its traditional medicinal use.
Keywords: Bioactive compounds; Garcinia cambogia; hydro-alcoholic extract; phytochemical profiling; therapeutic potential